2023
DOI: 10.3390/nu15030525
|View full text |Cite
|
Sign up to set email alerts
|

Is Generation Z Ready to Engage in Entomophagy? A Segmentation Analysis Study

Abstract: This study examines the behavior and attitudes of adult Generation Z cohort members in relation to entomophagy. Specifically, it explores their familiarity with insect consumption, prior experience, and willingness to consume certain insect-based foods and drinks. Lastly, the Z cohort is segmented based on their behavior and attitudes. Through online quantitative research, a valid sample of 742 questionnaires was collected. Data analysis included descriptive statistics, reliability analysis, factor, hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 121 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…Paramount research in recent years has been devoted to this topic, showing that consumers are mostly skeptical about some possible alternative proteins such as those derived from insects. This is confirmed by the study conducted by Kamenidou and colleagues [12] with a large sample of Greek participants. Their results show that the young subjects who responded to their survey-all belonging to the so-called Generation Z-are generally not willing to substitute traditional meat proteins with insect-based alternatives.…”
supporting
confidence: 74%
“…Paramount research in recent years has been devoted to this topic, showing that consumers are mostly skeptical about some possible alternative proteins such as those derived from insects. This is confirmed by the study conducted by Kamenidou and colleagues [12] with a large sample of Greek participants. Their results show that the young subjects who responded to their survey-all belonging to the so-called Generation Z-are generally not willing to substitute traditional meat proteins with insect-based alternatives.…”
supporting
confidence: 74%
“…Cicatiello et al [4] also showed that gender (male) positively influenced consumer attitudes towards entomophagy. In contrast, Kamenidou et al [3] found that gender did not offer any statistically significant differences across the segments that emerged in their research.…”
Section: Literature Reviewmentioning
confidence: 66%
“…There are conflicting results in studies of generational cohorts and entomophagy in the Western world, as some have found that all generational cohorts, including the Z-cohort, have a low propensity to consume insects [3,9,12], and some others have found that there is already a market segment ready to adopt insect consumption in their daily diet [11], especially for the generational cohorts Y and Z [13].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation